Biopsy-Proven Acute Tubular Necrosis due to Vancomycin Toxicity. (31st May 2011) - Shah-Khan, Farheen; Scheetz, Marc H.; Ghossein, Cybele
Abstract : Vancomycin (VAN) has been associated with acute kidney injury (AKI) since it has been put into clinical use in the 1950's. Early reports of AKI were likely linked to the impurities of the VAN preparation. With the advent of the more purified forms of VAN, the incidence of AKI related to VAN were limited to acute interstitial nephritis (AIN) or as a potentiating agent to other nephrotoxins such as Aminoglycosides. VAN as the sole etiologic factor for nephrotoxic acute tubular necrosis (ATN) has not been described. Here, we report a case of biopsy-proven ATN resulting from VAN.